Improvisation. Everywhere. The Oxford Handbook of Critical Improvisation Studies (KULT_online, 2017)
Georges E. Lewis’ and Benjamin Piekut’s Oxford Handbook of Critical Improvisation Studies is another step toward the scientific institutionalization of a hitherto rather informal discourse. The two volumes are proof of both the heterogeneity and the particular potential of this field of research. That improvisation is more than just a particular artistic practice but the core of creativity as such and hence of any praxis, is implicit to the handbook’s overall conception as well as to most of its contributions. That way, however, the project also touches on the wider question: whether improvisation has to be understood aesthetically or primarily from an ethical standpoint.